STRATEGY OF THE HOUSING AND SETTLEMENT SERVICE IN HANDLING SLUM AS AN EFFORT TO CREATE A HEALTHY ENVIRONMENT IN BANJAR CITY - Rifki Agung Kusuma Putra,; Ari Kusumah Wardani, (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
One of the challenges faced by the government is how to organize slum settlements, especially in areas that are growing quite rapidly. Slums are residential areas whose quality is very unfit for habitation. Because, on the other hand, slums are not only a problem but also one of the pillars that supports the urban economy, slums continue to be a challenge for district or city governments at this time which is happening in several villages/kelurahans in the city of Banjar. The purpose of this research is to find out how the Housing and Settlements Service deals with slum settlements in an effort to make Banjar City a healthier place. This study used a qualitative descriptive research method with data collection methods such as interviews, observation, and documentation. This study shows that revitalization is an increase in vitality by improving environmental quality. This aims to improve and encourage the regional economy by using existing facilities and infrastructure. Slums are housing and settlements that do not have basic facilities such as clean water, sanitation (latrines), waste management systems and rainwater gutters and are not well planned, integrated or planned. Slums are the term used to describe this type of community.